Cognitive Biases in Critical Decisions Facing SME Entrepreneurs: An External Accountants’ Perspective - Arno Nuijten; Nick Benschop; Antoinette Rijsenbilt; Kristinka Wilmink (Administrative Sciences, 2020)
Decisions by small and medium enterprise (SME) entrepreneurs are plagued by a variety of cognitive biases. Extant literature has mainly focused on a limited number of important biases (e.g., overconfidence) in a handful of important entrepreneurial decisions (e.g., start-up, market entry or exit). However, putting the spotlight on a few important biases and entrepreneurial decisions could leave other important biases and decisions underexposed. SME accountants are in a unique position to shed a broader light on this issue. SME entrepreneurs often seek advice of their accountants when they struggle with decisions that involve uncertainty and business risks in the domains of strategy, regulatory compliance, human resources, IT, and succession. In this study, we explore 12 different biases and analyze whether their importance can change across these decision domains. Interviews were performed with 14 SME accountants who provide an independent third-party view on decision making by over 3000 entrepreneurs. Our findings suggest that the importance of most of these biases varies from one decision domain to the other. We also identified four approaches (warn, inform, intervene, and coach) that accountants can take when entrepreneurs may fall victim to biases. We discuss the implications for research and practice of SME entrepreneurs and their accountants.